Pengaruh harga komoditas global terhadap industri reksa dana Indonesia - Nugraha, Handy; Putriani, Santi; Gustinanda, Mega Mustika; Makarim, Zaki Anwar (Nur Science Institute, 2023)
The mutual fund industry continues to show an upward trend, in contrast to the fluctuating macroeconomic and stock market conditions due to various negative sentiments and economic turmoil, such as the COVID-19 pandemic. This condition is presumably due to investment managers' success in diversifying investment portfolios in various assets. Diversifying and strategically allocating funds to various assets in the mutual fund industry are related to many variables, not just determinants. This study aimed to analyze the effect of global commodity prices such as gold, world crude oil, nickel, and palm oil on the net asset value of Indonesian mutual funds. The composite stock price index and interest rates are used as control variables. This study uses a quantitative approach using the VECM (Vector Error Correction Model) method. The data used is secondary data for 2013–2022, with a monthly frequency. The analysis results show that, in the long term, global commodity price variables significantly affect the net asset value of Indonesian mutual funds. In contrast, global commodity price variables do not significantly affect the short term.